(untitled) (Raparin Journal of Humanities (RJH), 2026)
Child protection is a progressive and systematic process. Among all local and public institutions and organizations, child protection has a profound and multidimensional interdependence. This process cannot be accomplished and protected by one entity; rather, it requires real and serious collaboration and contribution by all related sectors within society. As a result of this engagement and collaboration, the development of healthy and productive individuals who can contribute meaningfully to the community will occur. This study is a multi-dimensional investigation into a general descriptive approach that has been used. The communities that mentioned in this research are composed of basic centers which are women’s and children’s reform centers in the Kurdistan Region located in (Sulaymaniyah, Erbil, and Duhok). The study sample constitutes of all children referred by the courts to rehabilitation schools whose data equals 40 juveniles (38 males and 2 females). A scale or measurement structure is designed in this study as the primary tool for data collection. The purpose of this study is to evaluate the child protection process within the reform institutions of the Kurdistan Region. School’s rehabilitation is one of the highest levels of child protection based on the findings of the research. Additionally, the study states that the approaches applied by the staff in dealing with the children in these institutions are commonly appropriate and positive. Furthermore, the research proves that the services and basic needs provided to the juveniles by the institutions are maintained at a satisfactory level.